Diagnosing and treating cortisol insufficiency in ICU - Mat Nor, Mohd Basri (2013)
Critical illness elicits a major stress response that activates the hypothalamic-pituitary-adrenal (HPA) axis. The diurnal variation is often lost. The criteria for determining which patients have an adequate response to severe stress and which have an inadequate response are arbitrary and controversial. Furthermore, cortisol metabolism and function may also be altered by other methods which include reduced cortisol breakdown, renal dysfunction, reduction in albumin and cortisol binding protein (CBP) and the effects of SIRS response on plasma cytokines. Absolute adrenal insufficiency is rare in critical care and the incidence is less than 3%. Assessing adrenal insufficiency or relative adrenal insufficiency (RAI) is challenging in the ICU. Laboratory assays of plasma cortisol concentration and ACTH stimulation test are unreliable in this setting. Although severe stress activates the HPA axis, dissociation between plasma corticotropin levels and cortisol levels may occur, marked by suppressed corticotropin levels and elevated plasma cortisol levels. Critically ill patients have a marked reduction in levels of CBP with proportional increases in free cortisol, which can diffuse into tissues. Levels of interstitial cortisol obtained by microdialysis in patients with sepsis correlated only moderately with total plasma cortisol levels. This observation suggests blood levels of cortisol poorly reflect the amount of hormone available to target tissues.